IMPACT OF DISTRESS LEVEL IN RIGHT ISSUE PRICING AND SHARE PERFORMANCE - Sadjiarto, Arja; Natadjaja, Michela; Sutikno, Fiona (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This research aims to observe the influence of distress level and leverage on right issue subscription pricing since previous studies mainly focused on the subscription price’s impact rather than its determinants. For further analysis, this research also evaluates the subscription price, distress level, and leverage’s influence on share performance.Research Methods. Data analysis technique employs multiple linear regression with Ordinary Least Square (OLS) method, utilizing data from 70 public listed companies which are recorded to have published right issue in Indonesia Stock Exchange during 2004 to 2022.Research Results and Findings. This research discovered that distress level influences the right issue subscription price, and the right issue subscription price significantly influences share performance. Thus, the result of this research may be utilized by companies which are distressed, high-leveraged, or in possession of the characteristics in line with the control variables to consider the most ideal subscription price as well as its implications to the companies’ share performance.